P314 Renal tract anomalies in children with congenital heart disease detected during the procedure of cardiac catheterization. (6th June 2017) - Cagli, Cagla; Erdem, Sevcan; Atmis, Bahriye; Bayazit, Aysun K.; Demir, Fadli; Demir, Hüsnü; Özbarlas, Nazan
Abstract : Congenital heart disease is the most common congenital condition diagnosed in children and extracardiac abnormalities are frequent among patients with congenital heart disease. Associated urinary tract anomalies in these children are frequently silent, even though potentially significant with a prevalence of 7.5% to 12%. Patients whom were being followed-up and diagnosed with renal anomaly during the procedure of cardiac catheterization in Çukurova University Faculty of Medicine in Balcali Hospital are studied. During cardiac cathetherization renal anomaly was detected in 78 of children with congenital cardiac defects.%28.5 of the detected renal anomalies in patients were bilateral. 29 of the patients detected with renal anomalies were female (%37.7) and 48 of them were male (%62.3). Detected renal anomalies were hydronephrosis in%24.7; pelvicalyceal dilatation in%16.8; hydroureteronephrosis in%15.5; double collecting tubule system in%11.6; renal agenesia in%11.6; bifid pelvis in%7.8; dilatation of renal calyx in%2.5; renal hipoplasia in%2.5 ; horseshoe kidney in%2.5; extra renal pelvis in%1.2; triple renal pelvis in%1.2; ureter dilatation in%1.2; cross ectopic kidney in%2.4; in%1.2 of the patients double calyx are detected. Herein, we emphasised the importance of obtaining abdominal cineradiograph of children in the procedure of cardiac cathetherization for the detection of urinary tract abnormalities.